The distribution and maturation of tertiary lymphoid structures can predict clinical outcomes of patients with gastric adenocarcinoma - Sun, Hui; Liu, Yuxi; Cheng, Wanjing; Xiong, Rong; Gu, Wenchao; Zhang, Xiaoyan; Wang, Xin; Wang, Xu; Tan, Cong; Weng, Weiwei; Zhang, Meng; Ni, Shujuan; et al. (Frontiers in Immunology, 2024)
Tertiary lymphoid structures (TLSs) are analogues of secondary lymphoid organs that contain various immune cells. The spatial distribution, maturation and composition of TLSs have differential effects on prognosis, and the roles of TLSs in gastric adenocarcinoma (GA) have not been revealed. Thus, we evaluated the prognostic value of TLSs in GA through analysis of bulk RNA sequencing (RNA-seq) data from public databases and validated our findings in tumour samples from the Fudan University Shanghai Cancer Center (FUSCC) cohort. The spatial distribution, maturation, and composition of TLSs in GA were analysed by reviewing H&E-stained sections and by multiplex immunofluorescence (mIF) staining. We found that TLSs, especially TLSs with germinal centres (GCs) and TLSs located in the invasive margin (IM), were correlated with prolonged overall survival (OS). Second, analysis of public RNA-seq data showed that high dendritic cell (DC) scores were a favorable prognostic factor in GA patients with high scores for both TLSs and GCs. In the FUSCC cohort, DC-LAMP+ DCs were significantly enriched in IM-TLSs with GCs, suggesting a potential correlation between the tumour immune activation milieu and the DC abundance. Third, compared to that in TLSs without GCs, the proportion of FOXP3+CD8+ Treg cells was significantly decreased in IM-TLSs with GCs, and the percentage of PD1+CD20+ B cells was significantly increased in TLSs with GCs. Our results demonstrate that the 4 spatial arrangement and maturation of TLSs significantly affect prognosis and indicate that TLSs could be a new additional factor for histopathological evaluation.